HUBUNGAN KETEPATAN ESTIMASI DURASI OPERASI DENGAN UTILISASI KAMAR OPERASI ELEKTIF DI INSTALASI BEDAH SENTRAL RSUD Dr. SAIFUL ANWARMALANG - Dian Dwi Utami; Reny Tri Febriani; Andi Surya Kurniawan (PPPM STIKES Banyuwangi, 2024)
The operating room is a vital service in hospitals. The quality of service from the operating room can be assessed from one indicator, namely operating room utilization. Utilization is the actual time required to carry out additional operations turnover (operation transfer time) divided by the available time, where turnover averages over 15 minutes. Estimation of the duration of surgery is an important factor in operating room utilization. The aim of this study was to determine the relationship between the accuracy of estimating the duration of surgery and the utilization of elective operating rooms in the Central Surgery Installation at RSUD Dr. Saiful Anwar Malang. This research method is a prospective cohort for 19 working days. The sampling technique uses total sampling. The results of the study were that almost all 284 operations (93.4%) were accurate in estimating the duration of the operation according to estimates, and the majority of 197 operating rooms (64.8%) had operating room utilization in the poor category. Data analysis uses Chi-Square which shows that the p-value is 0.007 <0.05, which means there is a relationship between the estimated duration of surgery and operating room utilization. Operating room utilization can be optimal if one of the factors can be met, namely the operation can be completed on time (on Time) which means the estimation of the duration of the operation must also be correct. Therefore, there is a need for synergy between multidisciplines in the operating room and management in setting schedules and standards for estimating the duration of operations and it is necessary to re-socialize the quality of the operating room for users of the operating room and the rooms involved in it, because part of the quality of the operating room is a factors that can influence operating room utilization.